Challenges, opportunities, and dimensions of cyber-physical systems - Krishna, P. Venkata, 1977-; Saritha, V., 1977-; Sultana, H. P., 1973-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book explores current trends and enhancements of CPS, highlighting the critical need for further research and advancement in this field and focusing on architectural fundamentals, interdisciplinary functions, and futuristic implications"--Provided by publisher.
Cyber physical systems (CPSs) -- CPS architecture -- Cyber physical system design -- Interconnection issues in CPS -- Cyber physical internet -- Network QoS in CPS -- CPS security -- Security issues of CPS -- Interoperability and communication issues in CPS -- Heterogeneous networking issues -- Heterogeneous mobile computing issues -- Scalable architecture for heterogeneous environment -- Network services -- Cyber physical control systems -- Cyber physical systems management.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 01/10/2015).
Keywords: Embedded computer systems; Embedded Internet devices; Internet of things; Ad hoc networks (Comptuer networks); CPS fundamentals; Cyber-physical internet; Design components; Heterogeneous environments; Prototype architecture; QoS management; Security issues; Wireless and ad hoc networks; Electronic books